Immunity-driven Comparative Advantage and its Palliative Effect on Social Health and Inequality: A Theoretical Perspective - Sugata Marjit; Gouranga G. Das (Global Labor Organization (GLO), 2023)
We propose a model of "trade" between high income and low-income groups where the rich being scared of the spread of infection hires the poor to engage them in exposure-intensive outdoor activities as workers in the household industry. People who endure hardships and sustain exposure to unhygienic conditions may develop stronger immunity to fight the ongoing pandemic than members of the privileged class. The low-income group has greater endowment of immunity to income and for the rich it is lower. If such exchange takes place, essentially less immune people are withdrawn from exposure intensive activities and are being substituted by more immune workers. Thus, the spread and fatality will reduce with such a trade. The greater is the inequality, the more would be demand for labor for such work resulting in greater volume of such trade between low income and high-income workers. Thus, spread of the disease will be lower for countries where inequality is high. Later under a general equilibrium setting, we show that, ceteris paribus, a pandemic with a significant threat of infection and fatality would mean greater demand for poor workers; their income would rise and inequality would decline. If the pandemic increases demand for the top skilled, such as the case with virtual activities and derived demand for low skilled, relative wage for the top and bottom would increase.
Keywords: D5; I18; J31; L8; N3; O1; 330; Covid; Exposure-intensity; Gig economy; Wage Inequality; Herd-immunity; Comparative Advantage; Welfare; General Equilibrium